Influence of the health status and other relevant factors on the quality of life of elderly people - Vesić, Zoran; Brkić, Miroslav; Tanasijević, Jelena; Milanović, Marko; Vukašinović Vesić, Milica (Vojnosanitetski pregled, 2022)
Background/Aim. The world population is aging rapidly. It has become a challenge to meet the vital needs of the elderly in big cities. The aim of the study was to investigate the influence of the health status as well as other relevant factors on the perceived quality of life in aged people in Belgrade, Serbia. Method. The survey was conducted in October 2019 on a representative sample of 764 people (39.9% male and 60.1% female) aged between 65 and 79 years (mean ± standard deviation = 72.68 ± 7.11 years) living in Belgrade. In the research, a questionnaire developed on the basis of the World Health Organization (WHO) methodology for age-friendly cities was used, aimed to explore 11 factors important for the elderly. Results. Factor of physical accessibility of community and socioeconomic factors were highly significant [χ2 (df = 3, n = 764) = 238.905; p < 0.001 and χ2 (df = 3, n = 764) = 207.571; p < 0.001, respectively] and explained 39.4% and 35% of variance of perceived quality of life, respectively. Social environment explained 24.6% of variance of perceived quality of life [χ2 (df = 4, n = 764) = 140.242; p < 0.001]. Health status had greatest explanatory power regarding perceived quality of life and explained as much as 46.7% of variance [χ2 (df = 8, n = 764) = 292.083; p < 0.001]. When the unique impact of health status on quality of life was analyzed, when other variables were controlled, health status explained 21.6% of the variance in addition to the variance explained by physical accessibility, socioeconomic status, and social environment. Conclusion. Although health status has the greatest impact on the perceived quality of life of older people, interventions on other life important domains such as physical accessibility, socioeconomic status, and social environment could have a positive impact on the perceived quality of life where health status alone could not be improved.